The Relationship of Risk Perceptions and Visit Intentions on Jakarta Tourist’s Behaviour (Case Study of Bali During 2nd Phase of Covid-19) - Serlinda, Nathania; La Are, Robert (Conference Series, 2021)
In the beginning of 2020, a highly infectious virus called Coronavirus that started in Wuhan, China hit various parts of the world including Indonesia especially, Jakarta as Jakarta has the highest number of active Coronavirus cases in Indonesia. Unfortunately, the tourism industry became one of the most severely affected sectors. This year, which is 2021, the world has entered the 2nd year of the pandemic Covid-19. However, even though Covid-19 has caused numerous negative impacts for Jakarta citizens, the number of domestic tourist in Bali was starting to increase in the first quarter of this year. Therefore, it raised a question whether is there any relationship between risk perceptions and visit intention towards Jakarta tourist’s behaviour during the 2nd year of pandemic. Quantitative research method with online questionnaire as the research instrument was conducted and 380 respondents were participated in this research. Thereafter, the data was analysed using SPSS and the results found that there is a strong negative relationship between risk perceptions and tourist behaviour. Besides, this study also found out that there is strong positive relationship between visit intentions and tourist behaviour.